Level of Knowledge Regarding the use of AED Machine among Railway Employees (International Journal of Nursing Care, 2020)
Automated external defibrillator is a portable electronic device that delivers an electric shock to the heartmuscles through the chest wall in order to resolve a normal heart rate. The AED will analyse the heart’selectrical rhythm and if it detects a rhythm likely to respond to a shock, it will charge itself ready to delivera shock.Aim: To assess the level of knowledge regarding the use of AED machine among the railway employees ina selected railway station at Kannur districts.Objectives: The objectives of the study are to,• assess the level of knowledge regarding the use of AED among railway employees• find the association between knowledge and selected demographic variables among railway employees.Methodology: The study was conducted to assess the knowledge regarding use of AED among the railwayemployees in a selected railway station at Kannur district. Non experimental quantitative approach was usedfor this study. A total of 30 samples were selected using convenient sampling technique. Formal writtenpermission was obtained from the authorities prior to the data collection process. The data was analyzed byusing both descriptive and inferential statistics on the basis of the objectives and hypothesis of the study.Result: The study showed that 6.66% of railway employees have good knowledge, 70% of employees havemoderate knowledge, 23.33% railway employees have poor knowledge regarding the use of AED and therewas no association between knowledge and selected demographic variables except year of experience of theemployees.
Keywords: Knowledge, AED, railway employees